Effects of type of nutrition on the chemical composition of camels milk and urine - Abdalla, Isam; Haroun, Eman; .Abdalla, Hayder (Gezira Journal of Agricultural Science, 2018)
Camel milk and urine have high nutritive values and therapeutic properties. The objective of this study was to find out the effect of camel nutrition on milk and urine chemical composition. A total of 30 she camels were selected from 6 herds, 3 from Elmanagil area and 3 from Tambool area. All camels belong to the Arabian type. The she- camels were in their first to third lactation and in the second to eighth month of lactation. The camel herds in Elmanagil area grazed grasses and browsed shrubs and trees of different types, mostly Acacias. Camels in Tambool area received concentrate ration (sorghum grains, groundnut cakes and wheat bran), and dry roughages in the form of sorghum stalks and Abusabien hay in the pens. Milk and urine samples were collected from each camel and subjected to chemical analyses. The results showed significant differences (P≤0.05) in milk and urine minerals content between the two areas. The Ca, K and Mg levels in urine were higher than milk, while Na level was higher in milk compared to that in urine. The minerals content in the urine of the camels found in Elmanagil area were significantly higher (P≤0.05) than Tambool area. There was significant difference (P≤0.05) in fat content between the milk of the camels found in the two areas. The fat content was significantly higher in the camel milk produced in Tambool area. It is recommended that camels browse on trees to produce high nutritive value milk and urine.    إشتهرت منتجات الإبل وخاصة اللبن والبول بقيمتها الغذائية العالية وخصائصها العلاجية. الهدف من هذا  البحث هو تقييم تأثير تغذية الإبل على التركيب الكيميائي ومحتوى المعادن في ألبانها وأبوالها. تم إختيار 30 ناقة من 6 قطعان من الإبل، ثلاثة من منطقة المناقل والثلاثة الأخرى من منطقة تمبول .جميع النوق تنتمي لنوع الإبل العربية. يتراوح موسم الإدرار لها ما بين الأول والثالث بينما تتراوح فترة الحليب ما بين الشهر الثاني والثامن. إعتمدت النوق الموجودة في منطقة المناقل في تغذيتها على المرعى الطبيعي وما به من نباتات وشجيرات واشجار مختلفه معظمها من نوع الاكاشيا، في أثناء فترة جمع العينات، بينما إعتمدت النوق الموجودة في منطقة تمبول على أعلاف مركزة  عاديه تحتوي على (حبوب الذرة والامبازات ونخالة القمح) وأعلاف خشنة (قصب ذرة وتبن ابو سبعين) قدمت لها داخل الحظائر. تم جمع عينات من اللبن والبول من كل النوق وتم تحليلها كيميائياً. أظهرت النتائج أن هنالك فروق معنوية (P<0.05)  في محتوى المعادن في البول واللبن بين المنطقتين. كما وجد أن مستوى Mg, K, Ca أعلى بكثير في البول منه في اللبن. بينما كان مستوى Na أعلى في اللبن. كما أظهرت النتائج أن هنالك فروق معنوية (P<0.05) في محتوى المعادن في البول بين المنطقتين وكان مستوى المعادن المختلفة في بول الإبل أعلى في منطقة المناقل مقارنة بمنطقة تمبول. كما أظهرت النتائج ان هنالك فروق معنوية (P<0.05) في محتوى  الدهن في  االلبن بين المنطقتين. حيث كانت نسبة الدهن أعلى في لبن الإبل المنتج في منطقة تمبول. توصي هذه الدراسه  في حالة الحاجة إلى مستويات عالية من العناصر المعدنية Ca, K, Na, Mg)) في ألبان وأبوال الإبل يفضل أن تعتمد الإبل في تغذيتها على المرعى الطبيعي والأشجار.